Holocene oceanographic changes in SW Labrador Sea, off Newfoundland. (February 2016) - Sheldon, Christina M; Seidenkrantz, Marit-Solveig; Pearce, Christof; Kuijpers, Antoon; Hansen, Mette J; Christensen, Eva Zilmer
Benthic foraminiferal assemblages supported by selected geochemical data from three marine sediment cores collected in Placentia Bay, SE Newfoundland, are used to construct an ~13, 000-year-long record of regional oceanographic changes in the SW Labrador Sea. The area is located in the boundary zone between the cold, ice-loaded Labrador Current (LC) in the north and the warm Gulf Stream (GS) waters to the south. After the Younger Dryas termination, the influence of GS-derived water increased and was further strengthened at 10.7 cal. kyr BP through enhanced northward flow of Atlantic water via the Slopewater Current. A short-term event of increased terrestrial input and water column stratification at 8.4 cal. kyr BP was likely linked to the distal drainage of glacial Lake Agassiz. After 7.3 cal. kyr BP, a stronger LC weakened the inflow of warmer subsurface waters from the GS. This may be explained by extensive meltwater release from ice sheets in Arctic Canada and is concurrent with a general shift in oceanographic conditions in the Labrador Sea region. Around 4.0 cal. kyr BP, conditions became more stable with a slight increase in salinity, indicating a decrease in meltwater transported via the LC. The Northern Hemisphere neoglacial cooling around 2.8 cal. kyr BP was characterized off SE Newfoundland by a further stabilization of the current system, dominated by the LC with some continued influx of GS water.